Minimal information for studies of extracellular vesicles (MISEV2023) - MISEV Consortium (2024)
Funding Information: The authors thank all members of the international EV research community for their support throughout the process of producing this document. Publisher Copyright: © 2024 The Authors. Journal of Extracellular Vesicles published by Wiley Periodicals, LLC on behalf of the International Society for Extracellular Vesicles.